Different Effects of Irrigation Water Salinity and Leaching Fractions on Pepper (Capsicum annuum L.) Cultivation in Soilless Culture - Gürgülü, Hatice; Ul, Mehmet Ali (Agriculture (Basel), 2024)
Pepper (Capsicum annuum L.) is one of the most important vegetables cultivated under greenhouse conditions in Turkey. Salinity problems are experienced in both the soil and irrigation water in agricultural areas. For this reason, soilless cultivation in greenhouses is increasing and important, meaning that salinity control must be conducted more effectively. The increase in soilless agriculture practices and salinity problems should be investigated and studies should be carried out to propose solutions to the problems experienced. In this study, the effects of different salinity levels and leaching fractions on the plant growth, yield, quality and water consumption of pepper grown in soilless cultures were determined. The experiment was carried out over four growing periods across two years. The adopted experimental design was a randomized split-plot design with three replications. Pepper plants were grown in a perlite and cocopeat mixture in 144 pots. The volume of the pots was 8 L and the pots were filled with a mixture of 4 L of perlite and 4 L of cocopeat. The plants were fed with a complete nutrient solution and their EC levels were used as the control treatment (S1: the EC value of the control was 1.4–1.5 dS m−1). The electrical conductivities of the solution in the other three treatments were increased to 2 (S2), 4 (S3) and 6 (S4) dS m−1 above the control by adding NaCl. We attempted to achieve two different leaching fractions (LR: leaching ratio) by means of weekly measurements, with 15–20% (LR1) or 35–40% (LR2) being applied at each salinity level. According to our results, there was no significant difference between the leaching fractions with respect to yield in any of the four growing seasons, but the yield decreased with the increase in salinity. The difference between the salinity level treatments and their interactions between the subjects was generally significant for the production periods.